Pengaruh Latihan El Rondo terhadap Peningkatan Keterampilan Passing Tim Futsal SMAN 3 Nganjuk - Muhammad Dandung Nur Arsaaha; Fahrial Amiq (Jurnal Bintang Pendidikan Indonesia, 2024)
Implement El Rondo training regularly and systematically to obtain maximum results in improving passing skills. This research aims to analyze the effect of El Rondo training on improving the passing skills of the futsal team at SMAN 3 Nganjuk. This type of research uses a Pre-Experimental Design using a One Group Pretest-Posttest Design research design with a total population of 20 male futsal players and 18 people were taken as samples, then a simple random sampling technique was used to determine the sample. The futsal team players at SMAN 3 Nganjuk received 16 El Rondo training sessions. The results of data analysis using the Paired Sample T-test show that El Rondo training influences the passing skills of the futsal team players at SMAN 3 Nganjuk. The pretest results showed an average passing skill of 8.56 and a posttest average of 11.56 resulting in an average increase of -3.000. Providing an increasingly structured training program can have an influence on improving passing skills. It is hoped that the El Rondo training program which is given regularly can improve the passing skills of the players.